Analysis of Culture Shock Levels Among 2025 Science Cohort Students in Relation to University Learning Patterns - Nasution, Ayyu Rizkia; Azizah, Fitri; Manullang, Hanna Mawarni; Fadilla, Raudatul; Siregar, Sania; Amanda, Tia Rahmatun (Journal of Education Religion Humanities and Multidiciplinary, 2025)
The transition from high school to university requires new students to adjust to more complex academic demands. This study aims to identify forms of academic culture shock and the learning adaptation strategies employed by first-year students in the 2025 Science Program. A quantitative descriptive method was used by analyzing students’ responses regarding changes in learning patterns, adjustments to learning strategies, and psychological factors experienced during the adaptation process. The results indicate significant shifts in learning patterns, particularly in learning styles, the need to modify learning methods, and the reorganization of study schedules. These shifts reflect the emergence of academic culture shock arising from the demands of more independent, analytical, and structured learning in higher education. Although students demonstrate adaptive capacities through improved learning strategies and time management, several challenges persist, such as decreased concentration, difficulty understanding new academic terminology, and hesitation to interact with lecturers. Beyond learning processes, culture shock also affects psychological well-being, including stress and academic anxiety. These findings highlight the need for more systematic academic support for new students.